Russian anti-semitism and the scapegoating of the Jews - Gibson, James L. 1951-; Howard, Marc Morje (Cambridge University Press, 2007)
Throughout Russian history, Jews have often been blamed when turmoil has arisen in the country. It is surprising, therefore, that Russian politics in the 1990s focused so little on Jews as a source of the political and economic crises afflicting the country. This article investigates anti-Jewish attitudes in Russia over time and cross-sectionally, carefully scrutinizing the hypothesis that perceptions of economic, social and political upheaval activate latent authoritarianism into anti-Semitism. Little if any support is found for the hypothesis and therefore it is argued that scapegoat theory, as currently constituted and applied to Jews, is too simplistic to be useful. Russian Jews were not subject to intolerance and repression in the 1990s because anti-Semitic beliefs were not widespread enough to be used successfully by political entrepreneurs seeking advantage through attacks on Jews.